2016
DOI: 10.3892/ijo.2016.3494
|View full text |Cite
|
Sign up to set email alerts
|

BAG3-mediated Mcl-1 stabilization contributes to drug resistance via interaction with USP9X in ovarian cancer

Abstract: Abstract. Paclitaxel in combination with carboplatin improves survival among patients with susceptible ovarian cancers, but no strategy has been established against resistant ovarian cancers. BAG3 (Bcl-2-associated athanogene 3) is one of six BAG family proteins, which are involved in such cellular processes as proliferation, migration and apoptosis. In addition, expression of BAG3 with Mcl-1, a Bcl-2 family protein, reportedly associates with resistance to chemotherapy. Our aim in this study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…BAG3 increases the invasiveness of uterine corpus and ovarian carcinoma (35,36). Recently, there has been evidence that revealed that downregulation of BAG3 can enhance the efficacy of chemotherapeutic drugs paclitaxel in ovarian clear cell carcinoma cells (37). Induction of BAG3 expression attenuates apoptosis (38), whereas decreasing its expression promotes apoptosis in various human cell models (39).…”
Section: Discussionmentioning
confidence: 99%
“…BAG3 increases the invasiveness of uterine corpus and ovarian carcinoma (35,36). Recently, there has been evidence that revealed that downregulation of BAG3 can enhance the efficacy of chemotherapeutic drugs paclitaxel in ovarian clear cell carcinoma cells (37). Induction of BAG3 expression attenuates apoptosis (38), whereas decreasing its expression promotes apoptosis in various human cell models (39).…”
Section: Discussionmentioning
confidence: 99%
“…The proto‐oncogenic role of MCL1 gene in OVC has been identified by various studies during the last decade . These studies not only reported the important antiapoptotic effects of MCL1 gene on OVC but also showed that this gene had a critical function in drug resistance of OVC.…”
Section: Discussionmentioning
confidence: 98%
“…These studies not only reported the important antiapoptotic effects of MCL1 gene on OVC but also showed that this gene had a critical function in drug resistance of OVC. MCL1 protein interacts with a wide spectra of other proteins to interfere with normal cell apoptosis such as deubiquitinating enzyme 3, ubiquitin‐specific proteases, and BH3‐only protein NOXA etc . The knockdown of MCL1 gene has also been proved to be an effective way of retarding OVC cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mcl‐1 is a well‐defined anti‐apoptotic protein. It has been reported that increased Mcl‐1 stabilization contributes to drug resistance in ovarian cancer cells . Conversely, inhibition of Mcl‐1 can sensitize ovarian cancer cells to chemotherapeutic agents .…”
Section: Discussionmentioning
confidence: 99%